Frontal fault location and most recent earthquake timing for the Alpine Fault at Whataroa, Westland, New Zealand. Issue 3 (3rd July 2018) - Langridge, Robert Max; Howarth, Jamie D.; Cox, Simon C.; Palmer, Jonathan G.; Sutherland, Rupert
ABSTRACT: Active traces of the reverse dextral Alpine Fault were poorly located on the true left (southwest) side of the Whataroa River. Mapping using airborne LiDAR-derived high resolution topographic data has identified a 300 m wide zone of partitioned faulting including the northeast-striking frontal trace of the Alpine Fault, c. 1.3 km northwest of the DFDP-2 drillsite. Excavation into a 1.2 m high, northeast-trending scarp exposed sheared gravels draped by folded fine-grained alluvial deposits relating to only the most recent faulting event. Sheared gravels within the trench exposure have fault fabrics dipping in the range of c. 45–65° to the southeast. Radiocarbon dates used in an OxCal model that incorporates dendrochronological results from trees that colonised the river floodplain following migration of the river constrain the timing of this faulting event to c. AD 1706–1823. Thus, faulting that formed this single-event scarp has been correlated to the well-known AD 1717 earthquake. The faulted terrace (tw4) was formerly the active floodplain of the Whataroa River, which reworked the surface post-AD 1717 before incising to its current bed level. The preferred fault dip from this frontal trace to the Alpine Fault target depth beneath the DFDP-2 drillsite is c. 46° to the southeast, which is consistent with the range of dips observed in the trench.